2014
DOI: 10.1073/pnas.1311846111
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput combinatorial screening identifies drugs that cooperate with ibrutinib to kill activated B-cell–like diffuse large B-cell lymphoma cells

Abstract: The clinical development of drug combinations is typically achieved through trial-and-error or via insight gained through a detailed molecular understanding of dysregulated signaling pathways in a specific cancer type. Unbiased small-molecule combination (matrix) screening represents a high-throughput means to explore hundreds and even thousands of drug-drug pairs for potential investigation and translation. Here, we describe a high-throughput screening platform capable of testing compounds in pairwise matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
278
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 352 publications
(286 citation statements)
references
References 52 publications
6
278
2
Order By: Relevance
“…Although secondgeneration Btk inhibitors with promising efficacy profiles have been developed (37,38), it is expected that combination regimens will result in long-lasting responses, as they may overcome resistance. Indeed, combining ibrutinib with a PI3K or Akt pathway inhibitor was shown to have synergistic effects (36,(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Although secondgeneration Btk inhibitors with promising efficacy profiles have been developed (37,38), it is expected that combination regimens will result in long-lasting responses, as they may overcome resistance. Indeed, combining ibrutinib with a PI3K or Akt pathway inhibitor was shown to have synergistic effects (36,(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have shown that the combination of Ibrutinib with the dual PI3K/mTOR inhibitor BEZ235 synergistically inhibits cell viability of ErbB2+ breast cancer cells. Recently, a synergistic interaction between Ibrutinib and a wide range of compounds targeting the PI3K/AKT/mTOR-signaling cascade, including BEZ235, was demonstrated in an activated B-cell-like subtype of diffuse large B-cell lymphoma [31]. The development of efficient drug combination regimes in the treatment of cancer is a promising therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In normal B-cells treated by ibrutinib, a decrease in the expression of other antiapoptotic proteins like BCL2A1 and Bcl-XL has been reported [20]. The effect of DXM/ibrutinib combination on lymphocyte cell death has already been observed in vitro in diffuse large B-cell lymphoma cell line in which ibrutinib input potentiated cell viability reduction [27]. Once again DXM addition to ibrutinib treatment could reinforce its activity and notably apoptotis induction via Syk inhibition and also Mcl-1 downregulation.…”
Section: Discussionmentioning
confidence: 97%